محكمة الجنایات الإستئنافیة في ظل قانون 17/07 بین تكریس مبدأ التقاضي على درجتین وجدواه - جعفر وفاء- زموري فاطمة الزھراء (جامعة المسيلة, 2021)
سعى المشرع الإجرائي الجزائري من خلال تعديل قانون الإجراءات الجزائية رقم 155/66 وذلك من خلال القانون 17/07 سنة 2017 الوصول لتكريس حقيقي لمبدأ التقاضي على درجتين في عموم مراحل التقاضي، ومن ثم إنشاء محكمة الجنيات الاستئنافية ووضعها قيد التنفيذ، فبعد أن كان هذا المبدأ يشمل المخالفات والجنح، أضحى يضم أخطر درجات الجرائم وهي الجنايات. فمحكمة الجنايات الإستئنافية تعد ضمانة قانونية للمتقاضين لتغير الأحكام الصادرة في المحكمة الجنائية الإبتدائية، وكذلك تصحيح الأخطاء التي يرتكبها القضاة في إصدار أحكامهم. Resume: The Algerian procedural legislator sought, through the amendment of the Code of Criminal Procedure No. 155/66, through Law 17/07 of 2017, to achieve a real consecration of the principle of litigation at two levels in all stages of litigation, and then the establishment of the Court of Appeals for Appeals and its implementation, after this principle was It includes infractions and misdemeanours. It now includes the most serious degrees of crimes, which are felonies. The Criminal Court of Appeal is a legal guarantee for the litigants to change the judgments issued in the Criminal Court of First Instance, as well as to correct the errors committed by the judges in issuing their judgments.
Keywords: محكمة الجنايات -الاستئناف -07/17-التقاضي